Material Properties of Various Cast Aluminum Alloys Made Using a Heated Mold Continuous Casting Technique with and without Ultrasonic Vibration - Mitsuhiro Okayasu; Yuta Miyamoto; Kazuma Morinaka (Metals, 2015)
This work was carried out to develop high-quality cast aluminum alloys using a new casting technology. For this purpose, commercial Al alloys were created by heated mold continuous casting (HMC) with ultrasonic vibration (UV). With the HMC process, the grain size and the crystal orientation of the Al alloys were controlled, i.e., fine grains with a uniformly organized lattice formation. In addition, an attempt was made to modify the microstructural formation by cavitation. These microstructural characteristics made excellent mechanical properties. Using UV in the continuous casting process, more fine and spherical grains were slightly disordered, which was detected using electron backscattered diffraction. The mechanical properties of the UV HMC Al alloys were slightly higher than those for the related cast Al alloys without UV. Moreover, the severe vibration caused higher mechanical properties. The lattice and dislocation characteristics of the cast samples made with and without UV processes were analyzed systematically using electron backscattered diffraction.